A model of introducing Clean Transport Zones in Poland – between optionality and obligatoriness (Discourse of Law and Administration, 2023)
Clean Transport Zones are a novelty in Polish legislation. It is true that the formal possibilityof introducing them should be bound by the Act of 11 January 2018 on electromobility andalternative fuels, nevertheless their actual establishment requires the adoption of an act of local law.Its proceedings are lengthy, hence only one such zone has been createds o far, in Krakow, in theKazimierz district, but eventually it was abolished. In the initial text, the act was very strict, the emphasiswas placed on zero emissions, hence the municipalities carefully used this instrument. Thechanges introduced in recent years, which can be considered significant, lead to the question whetherthe introduction of these zones should not be obligatory, as the deterioration of air quality is anobjective value, or whether, as a result of flexibility, leave them optional.
Keywords: local government; clean transport zones; clean air; climate protection